VALORISASI PENNISETUM PURPUREUM DAN TYPHA LATIFOLIA POST-FITOREMEDIASI LIMBAH TEKSTIL MELALUI ANAEROBIC DIGESTION SEBAGAI REINFORCEMENT BIODEGRADABLE FOAM - Wiliana, Angelica
Within the development of commercial phytoremediation technology in Indonesia, research on the different prospects of the post-phytoremediation plant valorization is ever more urgent. In this research, P. purpureum dan T. latifolia are phytoremediators to textile wastewater. Post-phytoremediation P. purpureum is then anaerobically digested to result in biogas and bioslurry. The solid fraction of the bioslurry is then dried and used as reinforcement to the gelatin-based biodegradable foam. The variation set at the phytoremediation stage includes the wastewater concentration (0 (control), 25, 60 %V/V). Variation set at the anaerobic digestion stage include the post-remediation plants which was planted on varying wastewater concentration. Variations set at the biocomposite manufacturing step is the amount of fiber added (0, 0,5, or 1 gram). It is found that phytoremediation using P. purpureum and T.latifolia results in higher percentage decrease for Cr, TDS, and TSS at wastewater concentration of 60 %V/V with value of 49, 62, and 95 % consecutively. P. purpureum reached the highest Relative Growth Rate (RGR) at wastewater concentration of 25 %V/V whereas T. latifolia reached highest at wastewater concentration of 60 %V/V, with the value of 0,034 and 0,04 consecutively. The Bio-Concentration Factor (BCF) value from P. purpureum and T. latifolia is highest at wastewater concentration of 60 %V/V, valuing to 0.16 and 0.1 consecutively. The Translocation Factor (TF) is highest at wastewater concentration of 60 %V/V valuing to 3.33 and 0.6 for P. purpureum and T. latifolia consecutively. Plant material is further processed through a 20 L anaerobic digester. The plant material from remediating 60 %V/V wastewater results in 3.69 L of biogas, largest amongst other variations. Cr concentration increases in both variations. Furthermore, for the biocomposite manufacture, the chosen variation is the addition of dried bslurry mass. The produced biocomposite is then tested for Ultimate Tensile Strength (UTS), elongation, elasticity modulus, density, water adsorption time, and biodegradability with the comparison of commercial flexible polyurethane foam. The highest Ultimate Tensile Strength (UTS) value is reached by sample with no additional fiber. Furthermore, the highest elongation capacity is reached by the sample with 0.5 gram reinforcement fiber. The biodegradable foam manufactured through this research possesses a density of 10x larger than that of commercial flexible polyurethane foam. All of the biodegradable foam samples within this research needs 7 days to completely degrade in soil. Based on the parameters mentioned, the biodegradable foam that is produced within this research cannot yet substitute commercial flexible polyurethane foam for packaging material.